2000
DOI: 10.1034/j.1600-0536.2000.042001001.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin hyporeactivity in relation to patch testing

Abstract: False-negative patch tests are clinically relevant. Skin hyporeactivity has been suggested as one possible cause. Evidence supports that failure to respond to a specific antigen might be due either to a faulty immune response, a defective inflammatory response or both. Thus, skin hyporeactivity may have clinical relevance in routine patch testing. Articles on this topic are infrequent and there is no index keyword for skin hyporeactivity as this phenomenon is poorly defined and investigated. This article summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…excited skin syndrome (28, 59), or hyporeactivity, i.e. silent back syndrome (60), subclinical sensitization (61), miscellaneous factors, such as cyclical variations throughout the menstrual cycle (62, 63), seasonal variations (65, 66), etc. All the above may account for inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…excited skin syndrome (28, 59), or hyporeactivity, i.e. silent back syndrome (60), subclinical sensitization (61), miscellaneous factors, such as cyclical variations throughout the menstrual cycle (62, 63), seasonal variations (65, 66), etc. All the above may account for inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…The background of false-positive test reactions is usually irritancy. A false-negative reaction can occur for a number of reasons: (1) failure to perform delayed readings, which is especially important for allergens known to elicit delayed reactions, and when testing elderly patients, who may present a protracted immunologic response; (2) the test concentration and/or the amount of the substance applied may have been insuffi cient; (3) the vehicle may not have released a suffi cient amount of the allergen (the biological availability was too low); (4) the patient's skin was unresponsive by prior sun exposure, local application of corticosteroids, and systemic administration of corticosteroids or immunosuppressors or other causes of skin hyporeactivity [ 104 ]; (5) the test site might have been inappropriate; (6) the occlusion might have been inadequate; and (7) there was an unsatisfactory replication by the test of the real exposure conditions (e.g., occlusion, heat, mechanical trauma, etc., that might enhance the percutaneous penetration of the allergens) or the skin penetration at the test site is lower than that of clinical exposure (e.g., eyelids, axillae, etc.). A false-positive reaction may be attributed to several causes, such as (1) testing with allergens that are marginally irritants, (2) testing with allergens at concentrations that exceed their irritancy thresholds, (3) spillover reaction from a nearby true positive reaction, (4) multiple simultaneous positive reactions, (5) testing patients with active dermatitis or otherwise sensible or irritable skin, and (6) testing with nonstandardized substances or substances of unknown irritant potential.…”
Section: The Problem Of False-positive and False-negative Patch Test mentioning
confidence: 99%
“…Skin hyporeactivity describes a general state of diminished skin response to various challenges, both irritant and allergic, exogenous or endogenous, which exist not only in patients with obviously immunomodulated diseases but also in normal subjects, whereas skin anergy may be defined as a diminished skin reactivity/impaired cellular immune response to one or more specific antigens/allergens, as seen in sarcoidosis (1, 2) and cancer patients (9). Koehler and Maibach (2) suggested that skin hyporeactivity could be a cause of false‐negative patch tests, which are clinically relevant and should not be overlooked. They also proposed the mechanisms of skin hyporeactivity, which might be the result of a faulty immune response or a defective inflammatory response, or both.…”
Section: Commentmentioning
confidence: 99%
“…It is possible that both the immune system and the inflammatory response are impaired. Unfortunately, the skin hyporeactivity occurred somewhat unexpectedly and we were unable to use the standardized irritant panel as a positive control (2) or to study the inflammatory biomarkers to validate the status of his skin. The nature of anergy in our patient has yet to be determined.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation